Hacia una tendencia modernista (simbolista): el drama Desolación (1917) de Enrique López Albújar - Ventura Vásquez, Williams Nicks (2018)
He studied the influence of modernism —which produced a reform in Spanish-American literature— in the Peruvian theatre with the drama Desolation (1917) by Enrique López Albújar, which manifests features of the nineteenth norms of the nineteenth century, but looks for new Parameters of representation, a new thematic content and an artistic quality in the language to determine the effect of modernism, under the Symbolist modality, in the Peruvian theatre. He examines this literary trend and analyses this theatrical piece from a semiotic and rhythmic view. The study contributes to the diverse researches on the modernism that allowed the artistic renewal in the poetry and the narrative and that on the theatrical creation were absent.